3(x-4)-12+2x-9=

Simple and best practice solution for 3(x-4)-12+2x-9= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(x-4)-12+2x-9= equation:


Simplifying
3(x + -4) + -12 + 2x + -9 = 0

Reorder the terms:
3(-4 + x) + -12 + 2x + -9 = 0
(-4 * 3 + x * 3) + -12 + 2x + -9 = 0
(-12 + 3x) + -12 + 2x + -9 = 0

Reorder the terms:
-12 + -12 + -9 + 3x + 2x = 0

Combine like terms: -12 + -12 = -24
-24 + -9 + 3x + 2x = 0

Combine like terms: -24 + -9 = -33
-33 + 3x + 2x = 0

Combine like terms: 3x + 2x = 5x
-33 + 5x = 0

Solving
-33 + 5x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '33' to each side of the equation.
-33 + 33 + 5x = 0 + 33

Combine like terms: -33 + 33 = 0
0 + 5x = 0 + 33
5x = 0 + 33

Combine like terms: 0 + 33 = 33
5x = 33

Divide each side by '5'.
x = 6.6

Simplifying
x = 6.6

See similar equations:

| 4.84x=2x | | (-3x-4)-(-2x-1)=6 | | 4(3x-5)+6=x | | 5g+14g+3= | | 4m-2=5m+7 | | 30x^2-85x+60=0 | | -2(5+6k)+16=-90 | | A^3-7a^2+6a-10= | | 4a+11-1a=2 | | 6x-4+2x-2=90 | | 42=7f | | 1300.4624=2*3.14*38.44+2*3.14*6.2*h | | -3(-10+6x)=30 | | x+13+2x+17=180 | | 1300.46=2*3.14*38.44+2*3.14*6.2h | | 80=-16t^2+35t+12 | | 6x=40+x | | 1300.46=2*3.14*38.44+2*3.14*6.2 | | -6(3+2x)=-8-2x | | y=5x-3+5x+2 | | 5(7+2x)=x-13+5x | | 0.4(x+70)+0.2x=6 | | D^2-36d+324=0 | | s=10p | | 8(7-m)=-24 | | 1300.46=2*3.14r^2+2*3.14*6.2 | | y=100+x+(7-x) | | y(15x-18)= | | 4x+7+3x-17=180 | | X=-16x^2+38 | | 2x-x^2=.91 | | 3b^2-4b-4= |

Equations solver categories